PENGARUH LATIHAN MENGGUNAKAN MEDIA KURSI TERHADAP TENDANGAN MAWASHI GERI BELADIRI KARATE - Alhinduan, Muhammad Hasan; Simanjuntak, Victor; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research problem was what is the influence of training with user chair media toward kick mawashi geri karate in SMA Negeri 7 Pontianak. The purpose was for knowing the influence practice with chair media toward with mawashi geri karate. The method used was qualitative method with experiment pre-experiment design. The population was taken all student extracurricular aggregate 10 people, with sampling jenuh. Analysis data was done with uji-t. The research result was: stage 1 average pretest with score 28 with posttest score 50 with value sig. 0,000 law more than alfha 0,05, then declared different real with percentage 41%, stage 2 average pretest score 28 and posttest score 52 with value sig. 0,000 law more that alfha 0,05, that declared different real with percentage 25%, stage 3 average pretest score 32 and posttest score 56 with value sig. 0,000 law more that alfha 0,05, that declared different real with percentage 83%. Conclusion from result kick mawashi geri can do as media practice.Â Keywords : Mawashi Geri, Media Chairs